(untitled) (Research, Society and Development, 2023)
The use of forest species is common for various purposes such as the production of furniture, watercraft, and by-products such as charcoal. Microorganisms are viable alternatives to increase the efficiency of seedling production of these species. The objective of the present work was to evaluate the efficiency of Trichoderma inoculants as a plant growth promoter in the species of Paricá (Shizolobium amazonicum), Fava-tamboril (Entererolobium maximun) and Amarelão (Apuleia leiocarpa). Two Trichoderma isolates were used: UFT-57 (Trichoderma virens) and UFT-21 (T. asperelloides). The isolates were picked in a petri dish with PDA medium (potato, dextrose and agar) and incubated in a B.O.D. chamber, at 27 °C ± 2 °C, for 12 hours with light, for seven days. At planting, the suspension with Trichoderma was placed with the aid of a graduated pipette, 1 mL was added in each tube, with the sowing of three seeds and later leaving one plant per tube. Plant height, stem diameter, root volume, shoot dry mass, root dry mass and Dickison’s quality index were evaluated. The T. asperelloides and T. virens isolates have a positive performance in the production of Paricá, Fava-tamboril and Amarelão seedlings, evidenced by the increase in biomass both in the root system and in the aerial part.